PELATIHAN PENERAPAN APLIKASI SCRACTH BERBASIS VISUAL PROGRAMMING LANGUAGE UNTUK MENINGKATKAN KETERAMPILAN LITERASI GURU DI SDN BELOH MOJOKERTO - Muhammad Saibani Wiyanto; Fitri Resti Wahyuniarti; Muhammad Bagus Ramadhan; Anthony Pradana; Rahma Amelia Putri; Santika Aliyah Firdaus (Nusantara Hasana Journal, 2025)
This community service program was conducted at Beloh Public Elementary School, Mojokerto, aiming to enhance teachers’ technological literacy skills through the use of Scratch, a visual programming language. The main problem faced by the partner school was the limited integration of technology in the teaching process, which remained largely conventional and less engaging for students. The implementation method consisted of needs analysis, module preparation, and intensive training delivered in three stages: introduction to Scratch, practical development of interactive learning media, and publication of the outputs for classroom application. The results indicate that teachers were able to design creative and interactive learning media that fostered greater student engagement. This program demonstrates that systematic mentoring can encourage teachers to be more innovative in integrating technology, while also establishing the foundation for continuous collaboration in improving the quality of elementary education. Key words: Technological literacy, Scratch, Learning media